Efektivitas Perawatan Luka Kronik Denganmetode Wound Healing Dressing Terhadap Penyembuhan Luka Ulkus Diabetikum Di Praktek Perawat Pusat Perawatan Luka, Stoma, Inkontinensia Asri Wound Care Center MedanTahun 2024 - Yusridawati , Yusridawati (Lembaga Dongan Dosen, 2025)
Diabetes mellitus is a chronic disease in which the pancreas does not produce enough insulin, blood sugar levels are regulated by the hormone insulin. As a result, people with diabetes mellitus experience peripheral neuropathy disorders, which cause damage to the peripheral nerves, leading to the occurrence of diabetic ulcers. Data on diabetic ulcers at the Wound Care Clinic, Stoma, Incontinence Asri Wound Care Center Medan in January-March were 58 people. Diabetic ulcers can be treated with proper wound care, one of which is with wound healing dressing techniques. The purpose of this study is to see if there is an Effectiveness of Wound Care with the Wound Healing Dressing Method on Wound Healing Diabetic Ulcers. This type of quantitative research is a quasi-experimental one group pre-posttest. The population of patients who treated wounds in June amounted to 21 people. The sampling technique uses purposive sampling. The measuring instrument uses the Winner Scale observation sheet. The statistical test is the Paired Sample T Test. The results of this study were before being given wound treatment with the wound healing dressing method in patients with diabetic ulcer wounds, which was moderate, with a mean (29.4667) and after moderate, with a mean (25.4667). The results of the analysis obtained a p-value of 0.000<0.005, meaning that Ho was rejected and Ha was accepted, which means that there is an Effectiveness of Chronic Wound Treatment with the Wound Healing Dressing Method on the Healing of Diabetic Ulcer Wounds in the Nurse Practice of the Wound Care Center, Stoma, Incontinence Asri Wound Care Center Medan. The conclusion of the study showed that there was an Effectiveness of Chronic Wound Treatment with the Wound Healing Dressing Method on Healing Diabetic Ulcer Wounds at the Asri Wound Care Center Clinic in Medan. It is hoped that this research can be a source of information for future researchers.